2021
DOI: 10.1093/elt/ccaa079
|View full text |Cite
|
Sign up to set email alerts
|

Addressing LGBTQ erasure through literature in the ELT classroom

Abstract: This article argues the case for the use of well-chosen literary texts as a means of addressing ongoing LGBTQ (lesbian, gay, bisexual, transgender, and queer or questioning) erasure in the ELT classroom. In this way LGBTQ students are offered much-needed recognition and those students who are not LGBTQ are given the opportunity to come to an understanding of those who are. Given the very different circumstances and constraints in which teachers work globally a distinction is made between explicitly queer texts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This promotes a more accepting classroom environment and helps educators and learners explore and challenge gender norms that have traditionally dominated ELT. Further, cis‐heterosexual students are given the space to better understand the lived realities of queer individuals through instructional materials and classroom discussions (Gray, 2021). However, while some participants reported having the freedom to use gender‐themed texts (e.g., queer readings) as a choice reading in their lessons, it somehow relegates LGBTQIA+ course materials and topics to the margins rather than making them an integral part of the curriculum (Page, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This promotes a more accepting classroom environment and helps educators and learners explore and challenge gender norms that have traditionally dominated ELT. Further, cis‐heterosexual students are given the space to better understand the lived realities of queer individuals through instructional materials and classroom discussions (Gray, 2021). However, while some participants reported having the freedom to use gender‐themed texts (e.g., queer readings) as a choice reading in their lessons, it somehow relegates LGBTQIA+ course materials and topics to the margins rather than making them an integral part of the curriculum (Page, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…However, they cited a lack of models, their limited knowledge of queer concepts, and possible stakeholder resistance as impediments to integrating a queer perspective. Gray (2021), in a recent study, argued that "LGBTQ erasure is a double injustice," meaning that non-LGBTQIA+ people are denied the opportunity to "see the world through different eyes" (p. 148) since LGBTQIA+ people are not recognized in the curriculum. To address this erasure, Gray suggested that teachers use gender-themed literary texts to give LGBTQIA+ students opportunities for self-affirmation through self-recognition and to enable non-LGBTQIA+ students to relativize their worldview and foster empathy for others.…”
Section: Queering Eltmentioning
confidence: 99%
See 1 more Smart Citation
“…Children's literature, for instance, could depict diverse aspects of gender and sexual identities (Hedberg, Venzo, & Young, 2020) and assist youth in identity formation and confirmation (Batchelor, Ramos, & Neiswander, 2018). Reading these texts could also help address LGBTQ+ erasure in ELT classes (Gray, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Children's literature, for instance, could depict diverse aspects of gender and sexual identities (Hedberg, Venzo, & Young, 2020) and assist youth in identity formation and confirmation (Batchelor, Ramos, & Neiswander, 2018). Reading these texts could also help address LGBTQ+ erasure in ELT classes (Gray, 2021).An opportunity to introduce Chinese learners to queer issues, and thus queer pedagogy, came when I (Teacher) taught a 2-year English language acquisition course. The course was a requirement of the International Baccalaureate Diploma Programme, a pre-college curriculum.…”
mentioning
confidence: 99%